KETERKAITAN MOBILITAS MASYARAKAT DENGAN KASUS COVID-19 DI PROVINSI NUSA TENGGARA TIMUR MENGGUNAKAN DATA GOOGLE MOBILITY REPORT - FX Gugus Febri Putranto; Christiayu Natalia (Jurnal Statistika Terapan (ISSN 2807-6214), 2021)
Efforts to control the spread of COVID-19 through restrictions on community mobility have an impact on various macro indicators of development target at the national and regional levels especially in Nusa Tenggara Timur Province. Based on data from Statistics Indonesia, the poverty rate, unemployment rate, Gini Ratio, economic growth and Human Development Index (HDI) were also affected by the COVID-19 pandemic. This study aims to explain the general description of macro indicators of development target in Nusa Tenggara Timur Province, as well as examine the relationship between community mobility and new cases of covid-19 during the implementation of the PPKM policy starting in July 2021. Community mobility data is sourced from big data Covid -19 Community Mobility Reports, while data on the number of COVID-19 cases sourced from the website covid19.go.id. To examine the relationship between community mobility and COVID-19 cases, the Pearson correlation is used. The results showed that the six categories of community mobility destinations, except parks, all had a significant correlation with the addition of new cases in Nusa Tenggara Timur Province. The higher mobility of the community, the lower the number of new cases. On the other hand, in residential areas, the higher the mobility, the higher the number of new cases.